(untitled) (Journal Genta Kebidanan, 2025)
Background: Baby mortality especially on neotatal period in Indonesia with the most prevalence cases were caused by low birth weight that indicates the imperfection of body organs including the lungs that caused by lack of nutrition for fetal growth during pregnancy. Objective: To analyze the birth weight with prevalence of asphyxia in Dr. H. Moch. Ansari Saleh Banjarmasin Hospital. Methods: This quantitative research with analytical survey and cohort retrospective approach was conducted to 87 newborn baby’s data in Dr. H. Moch. Ansari Saleh Banjarmasin Hospital’s medical record that has been taken by simple random sampling technique and analyzed with chi square correlation test. Results: Majority of newborn baby have risky birth weight on 45 baby (51,7%) and suffered asphyxia on 50 baby (57,5%). Hypothesis test bivariately showed p value = 0,000. Conclusion: There is a correlation of birth weight with prevalence of asphyxia in Dr. H. Moch. Ansari Saleh Banjarmasin Hospital.